The Role of an Entrepreneur in Developing an Organizational Culture Fostering Innovations - Śmigielska , Grażyna (Studia Oeconomica Posnaniensia, 2016)
The paper examines the role of an entrepreneur in developing an organizational culture which could contribute to sustaining a competitive advantage based on innovation. Early concepts of an entrepreneur and his role in the economy as well as the contemporary concept of corporate entrepreneurship are presented. The attempt is made to link these concepts by the corporate culture which should foster corporate entrepreneurship. It then presents Wal-Mart as an example of a culture fostering entrepreneurship based on innovation. Findings suggest that entrepreneurship embedded in corporate culture is crucial for achieving sustainable competitive advantage and should be developed from the moment of the company foundation. The main values which fostered company success should be maintained whereas the way of implementing them should be changed along with changes in and outside the organization. The paper contributes to the theory as well as to business practice with reference to sustaining competitive advantage based on an entrepreneurial corporate culture. Past research does not emphasize enough the development of entrepreneurship culture, which allows an organization to sustain its growth after the entrepreneur’s death. This problem should be tackled by scientists in the management field.